GELOMBANG LONGITUDINAL - Amalia Audia; Rini Dalimunthe (JURNAL ILMIAH PENELITIAN MAHASISWA, 2025)
This study aims to introduce and explain the basic concepts of longitudinal waves and demonstrate their benefits in everyday life. Longitudinal waves are a type of wave whose direction of vibration is parallel to its direction of propagation, and they are most commonly found in sound. This study was conducted using a literature review method, which involved collecting various sources from physics textbooks, scientific articles, educational journals, and online documents. The research steps include information collection, scientific analysis, the development of easily understandable materials, and the drawing of conclusions regarding the benefits of longitudinal waves. The results of the study indicate that longitudinal waves are highly significant as they are utilized in various aspects of life, such as sound communication, musical instrument and recording technology, healthcare through ultrasound, security systems via sound sensors, and even in earth sciences like earthquake detection. These waves function through alternating compression and rarefaction that carry energy through a medium such as air, water, or solid objects. Examples of their application include human speech, wind instruments, waves on springs, and earthquake waves. Understanding longitudinal waves is not only beneficial for students in grasping physics lessons but also important for recognizing how energy and information move around us. Therefore, understanding longitudinal waves is crucial for both educational purposes and real-life applications.